2018
DOI: 10.1155/2018/8194721
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Compounds, Antioxidant, and Cardioprotective Effects of Pomace Extracts from Fetească Neagră Cultivar

Abstract: Grape pomace is a potential source of natural antioxidant agents. Phenolic compounds and antioxidant and cardioprotective properties of fresh and fermented pomace extracts obtained from Vitis vinifera L. red variety Fetească neagră grown in Romania in 2015 were investigated. Grape pomace extracts total phenolic index, total tannins, total anthocyanins, proanthocyanidins, flavan-3-ol monomers, stilbenes, and DPPH free radical scavenger were measured. The effect of a seven-day pretreatment with grape pomace extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 65 publications
4
57
0
Order By: Relevance
“…Younis et al reported that ISO in a dose of 85 mg/kg bw decreased in P wave, QRS complex, PR segment, and RR intervals and increased in the QT interval duration and ST-segment deviation, in comparison with the control rats (20). According to results of Soraya et al rats from AMI group treated with ISO in a dose of 100 mg/kg bw showed a marked decrease in R-amplitude, a significant decrease in the RR interval and therefore, a significant increase in the heart rate (21 (13). Rats with ISO-induced AMI had higher levels of CK, CK-MB, ( Table 2) compared to normal rat.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Younis et al reported that ISO in a dose of 85 mg/kg bw decreased in P wave, QRS complex, PR segment, and RR intervals and increased in the QT interval duration and ST-segment deviation, in comparison with the control rats (20). According to results of Soraya et al rats from AMI group treated with ISO in a dose of 100 mg/kg bw showed a marked decrease in R-amplitude, a significant decrease in the RR interval and therefore, a significant increase in the heart rate (21 (13). Rats with ISO-induced AMI had higher levels of CK, CK-MB, ( Table 2) compared to normal rat.…”
Section: Discussionmentioning
confidence: 93%
“…None of the doses of ISO influenced the PR interval ( Table 1). All ISO-induced ECG AMI-like alterations mentioned above could be due to the secondary loss of action potential in the cardyomyocites, as a result of oxidative stress (13). Oxidative stress plays an important role not only in AMI but also in many other cardiovascular disorders (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2. Phenolic compounds exhibit a wide range of physiological properties, such as anti-allergenic, anti-atherogenic, anti-inflammatory, antimicrobial, antioxidant, anti-thrombotic, cardioprotective and vasodilatory effects 8,9,10,11,12 .…”
Section: Fig 1: Plant Of Gynura Crepioidesmentioning
confidence: 99%